The block design subtest of the Wechsler adult intelligence scale as a possible non-verbal proxy of cognitive reserve - Corujo-Bolaños, Graciela; Yánez-Pérez, Roraima; Cedrés, Nira; Ferreira, Daniel; Molina, Yaiza; Barroso, José (Frontiers in Aging Neuroscience, 2023)
Objectives: To investigate the potential of the Block design subtest of the Wechsler Adults Intelligence Scale as a non-verbal proxy of cognitive reserve. Method: A total of 391 cognitively unimpaired participants were included in this study. The association between the Block design subtest and the Information subtest (an established verbal proxy of cognitive reserve) from the WAIS, as well as the association of the two subtests with a Cognitive Reserve Questionnaire (CRQ) were tested. In addition, multiple linear regression models were conducted to investigate the association of the Block design and Information subtests with cognitive performance. The capacity of the Block design subtest to minimize the negative effect of an older age over cognitive performance was also assessed and this effect was compared with that of the Information subtest. The four cognitive domains included were: verbal memory, visual-visuospatial memory, executive-premotor functions and processing speed. Results: The Block design subtest correlated positively with both the Information subtest and the CRQ. A statistically significant association was observed between the Block design subtest and all four cognitive domains. Higher scores in the Block design subtest minimized the negative effect of aging on the cognitive domains of visual-visuospatial memory and executive-premotor functions, in a similar way to the results obtained for the Information subtest. Conclusions: The Block design subtest is significantly correlated with two established proxies of cognitive reserve: it correlates with cognitive performance and high scores in Block design have the capacity to minimize the negative effect of an older age on cognitive performance. Therefore, the results suggest that the corrected Block design subtest could be considered as a non-verbal proxy of cognitive reserve.